Two reversible enantiotropic phase transitions in a pentacoordinate silicon complex with an O, N, O′‐tridentate valinate ligand. Issue 6 (1st June 2015) - Schwarzer, Anke; Fels, Sabine; Böhme, Uwe
<x xml:space="preserve">Abstract</x> Dimethyl[N‐(4‐oxidopent‐3‐en‐2‐ylidene)valinato‐κ3O, N, O′]silicon(IV), C12H21NO3Si, (II), crystallizes in the orthorhombic space group P212121. The chiral compound undergoes two sharp enantiotropic phase transitions upon cooling. The first transformation occurs at 163 K to yield a unit cell with one axis having double length. This intermediate‐temperature form has the monoclinic space group P21. The second transition takes place at 142 K and converts the single crystal into the low‐temperature form in the orthorhombic space group P212121. This transition proceeds under tripling of the a axis of the high‐temperature form. Both phase transitions are fully reversible and correspond to order–disorder transitions of the isopropyl group of the valine unit in the ligand backbone. The phase transitions presented here raise questions, since they do not fit into the rules of group–subgroup relationships.